PENGARUH CURRENT RATIO DAN DEBT TO ASSETS RATIO RETURN ON ASSETS PADA PT INDOCEMENT TUNGGAL PRAKARSA TBK Tahun 2013-2023 - Marsha Dava Daradinanti; Yulian Bayu Ganar (Journal of Research and Publication Innovation, 2025)
This research aims to determine the effect of the Current Ratio and Debt To Assets Ratio on Return On Assets at PT Indocement Tunggl Prakarsa, Tbk in 2013 - 2023, both partially and simultaneously. The research method uses descriptive analysis methods with a quantitative approach. The data collection method used in this research is secondary data. Secondary data taken is the financial report of PT Indocement Tunggal Prakarsa, Tbk. From the results of the Partial Test (T Test) of Current Ratio on Return On Assets, tcount>ttable is 6.420>2.36462 and the significance value is 0.001>0.05, so partially the Current Ratio variable has a significant effect on the Return On Assets variable. Meanwhile, the Debt To Assets Ratio towards Return On Assets shows a value of tcount <ttable, namely 3.420<2.36462 and a significant value of 0.008<0.05, so partially the Debt To Assets Ratio variable does not have a significant effect on the variable Return On Assets. Based on the F Test, the Current Ratio and Debt To Assets Ratio simultaneously have a significant effect on Return On Assets. It can be seen that the calculated F is greater than the F table, namely 7.261>4.74 and the significant value is 0.001>0.05, meaning that the variables Current Ratio and Debt To are simultaneous. Assets Ratio has a significant effect on the Return On Assets variable.